2019
DOI: 10.1038/s41746-019-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

City-wide electronic health records reveal gender and age biases in administration of known drug–drug interactions

Abstract: The occurrence of drug–drug-interactions (DDI) from multiple drug dispensations is a serious problem, both for individuals and health-care systems, since patients with complications due to DDI are likely to reenter the system at a costlier level. We present a large-scale longitudinal study (18 months) of the DDI phenomenon at the primary- and secondary-care level using electronic health records (EHR) from the city of Blumenau in Southern Brazil (pop. ≈340,000). We found that 181 distinct drug pairs known to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 44 publications
(76 reference statements)
5
24
0
1
Order By: Relevance
“…A Danish study of 167 232 patients from 1998 on the island of Funen found that 4.4% of all inhabitants of age above 70 were prescribed drug combinations with a high risk of severe interactions 43 . A recent Brazilian study with ~340 000 patients from primary‐ and secondary‐care hospitals arrived at a similar figure 44 . These estimates are substantially lower than our 14% patients prescribed pDDIs with expected major clinical significance (Table 3), likely because our data are newer than those in the former and include also tertiary hospitals unlike both those studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A Danish study of 167 232 patients from 1998 on the island of Funen found that 4.4% of all inhabitants of age above 70 were prescribed drug combinations with a high risk of severe interactions 43 . A recent Brazilian study with ~340 000 patients from primary‐ and secondary‐care hospitals arrived at a similar figure 44 . These estimates are substantially lower than our 14% patients prescribed pDDIs with expected major clinical significance (Table 3), likely because our data are newer than those in the former and include also tertiary hospitals unlike both those studies.…”
Section: Discussionsupporting
confidence: 68%
“…43 A recent Brazilian study with ~340 000 patients from primary‐ and secondary‐care hospitals arrived at a similar figure. 44 These estimates are substantially lower than our 14% patients prescribed pDDIs with expected major clinical significance (Table 3 ), likely because our data are newer than those in the former and include also tertiary hospitals unlike both those studies.…”
Section: Discussionmentioning
confidence: 57%
“…The data includes eighteen months (Jan 2014-Jun 2015) of anonymized drug administration and patient demographics retrieved from Pronto. It is the same data used in Correia et al [5] except for the removal of ophthalmological drugs, topical drugs, and vaccines from the analysis. In total, we analyze 140 unique DrugBank IDs dispensed to 133,047 patients.…”
Section: Data -Blumenaumentioning
confidence: 99%
“…More than 30% of ADR are caused by drug-drug interactions (DDI) that can occur when patients take two or more drugs concurrently (polypharmacy) [35]. The DDI phenomenon is also a worldwide threat to public health [1,67], especially with increased polipharmacy in aging populations.…”
Section: Pharmacovigilancementioning
confidence: 99%
“…Due to the widespread digitization of behavioral and medical data, the advent of social media, and the Web's infrastructure of large-scale knowledge storage and distribution there has been a breakthrough in our ability to characterize human social interactions, behavioral patterns, and cognitive processes, and their relationships with biomedicine and healthcare. For instance, electronic health records of entire cities can yield valuable insights on gender and age disparities in health-care [1], and the communication patterns of Twitter and Instagram help us detect the spread of flu pandemics [2], warning signals of drug interactions [3], and depression [4].…”
Section: Introductionmentioning
confidence: 99%